Structural and Phytochemical Investigation of Water Soluble Polysaccharide Isolated from Cassia Senna Tora (L.) Seeds: Characterization of galactomannans from Cassia Senna Tora seeds (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Senna tora (L.) (Family Fabaceae) is a fast growing and spreading Indian shrub. Senna tora produces in rural area of Bastar, Bilaspur, Durg, and Sarguja district of Chhattisgarh, India The Sarguja District accounts for more than 60 of the Charota production of the State. The seeds have been found to be an alternative source of commercial gums and are used as an anthelmintic, digestive, and to treat piles, skin diseases, and abdominal troubles. The present investigation deals with isolation, puriﬁcation and characterization of galactomannans from the seeds of Senna tora. Gum obtained from the seeds of S. tora is known as ‘Panwar gum’. Chemically it is neutral heteropolysaccharide of D-galactose and D-mannose with molar ratio 34. The galactomannan extraction was based on mechanical separation of the endosperm, water dissolution, centrifugation and precipitation with acetone. The characterized polysaccrides from the gum has the basic structure of galactomannans with a main chain of (1→4)-linked β-D-mannopyranosyl units to which single α-(1→6)-D-linked galactopyranosyl units.